Acute necrotizing esophagitis presenting with severe lactic acidosis and shock. Issue 4 (2nd October 2018) - Iwuji, Kenneth; Jaroudi, Sarah; Bansal, Arpana; Rivas, Ana Marcella
Abstract: Acute necrotizing esophagitis, also known as "black esophagus, " is typically characterized by a circumferential, friable black mucosal surface and preferentially involves the distal esophagus. It predominantly affects elderly men and presents as an upper gastrointestinal bleed. We describe a 60-year-old man with an acute upper gastrointestinal bleed and sepsis and subsequently acute necrotizing esophagitis.